Correlates of Self-Reported Incarceration Among Homeless Gay and Bisexual Stimulant-Using Young Adults. (June 2015) - Nyamathi, Adeline; Reback, Cathy J.; Salem, Benissa E.; Zhang, Sheldon; Shoptaw, Steven; Branson, Catherine M.; Leake, Barbara
Gay and bisexual (G/B) homeless adults face multiple challenges in life which may place them at high risk for incarceration. Yet, little is known about this understudied population in terms of risk for incarceration. Baseline data collected from a longitudinal study between October 2009 and March 2012 in Hollywood, California, explored correlates of self-reported incarceration among G/B homeless stimulant-using adults ( N = 353). Findings revealed older age, less education, having children, as well as a history of injection drug use and being born in the United States were positively associated with incarceration. Moreover, having poor social support and having received hepatitis information were also correlated with a history of incarceration. Our findings help us gain a greater awareness of homeless G/B adults who may be at greater risk for incarceration, which may be used by health care providers to design targeted interventions for this underserved population.